PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN NON MEDIS PADA RSUD dr. RM PRATOMO BAGANSIAPIAPI - Asri Kusuma Dewi; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
An important problem faced by leaders is how to increase morale so that they can support the succes of achieving goals. Trying to maintain the enthusiasm of employes so they can work hard. This research was conducted at RSUD dr. RM. Pratomo Bagansiapiapi.This study aims to determine and analyze the effect work discipline and work environment on non-medical employes work spirit morale partially and simultan.work discipline (X1) and work environment (X2) as independent variable and work spirit (Y) as the depedent variable.The problem in this study is the fluactive decline in employe morale accompanied by high employee absenteeism.The sample of this research was taken as many as 50 respondents and technique used was accidental sampling.The data obtained from the results of the questionare and then processed and then tested statistically through the SPSS program.From the results of the conducted,it shows that the participatory leadership style and work environment have a positive and significant effect on employee morale at RSUD dr. RM. Pratomo Bagansiapiapi Keywords : Work Discipline,Work environment and Work Spirit